Pemanfaatan Sistem Informasi sebagai Pendukung Integrasi Data - Sharazita Dyah Anggita; Eli Pujastuti; Ika Asti Astuti; Atik Nurmasani -; Anggit Dwi Hartanto (JITER-PM (Jurnal Inovasi Terapan - Pengabdian Masyarakat), 2024)
Utilization of technology in an institution can be done with many alternatives. One of them is through the use of information systems to support business processes. Data management and data archiving have different provisions and methods between work units and data is owned by each work unit. This difference results in data not being integrated and difficulty finding data when needed. The solution is that archiving and data management is carried out centrally through a website information system to support business processes. The method used consists of analyzing collaborators needs, creating an information system, demoing an information system, installing an information system, and evaluating the use of an information system. The formulated requirements can be used as a basis for creating an information system as a data integration center. The result of information system is demonstrated to collaborators to obtain feedback. The final result of the information system needs to be installed to be installed online so it can be used by collaborators to get feedback of the use the information system. The features in the available information system can help work units archive and manage data easily. Yayasan admins can access work unit data online as needed.